A review of intra-uterine death from 2013 till 2017 in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan - Singh, Aashreena Randhawa Mohinder (2022)
Retrospective review of intrauterine death in Hospital Universiti Sains Malaysia (USM) from 1st of January 2013 until 31st of December 2017. The current study aims to look at the causes and factors associated with intrauterine death (IUD) in a teaching hospital from the1st of January 2013 until the 31st of December 2017. STUDY METHOD: This retrospective study involved 174 patients. All mothers who presented with IUD occurring after 22 weeks of period of amenorrhea and gestation in Hospital USM from 1st of January 2013 until 31st of December 2017 were included. Social demographic data of the mothers were collected and data were reviewed for causes and risk factors associated with IUD. RESULT: Mothers in the age group of 25 till 29 years old had the highest number of IUD at 31 % (n=54) with primigravida’s recording the highest number of IUD at 41.95 % (n= 73). The main causes which lead to IUD were infection (n=58) 33.3 %, unexplained causes (n=47) 27.7 % ,congenital anomalies (n=45) 25.9% , placental abruption (n=15) 8.62% and trauma (n=9) 5.2% The risk factor associated with IUD in this study were pre-gestational / gestational diabetes mellitus at 25.86 % (n=45) , hypertensive disease 14.4% (n=25) , history of previous IUD 11.5% (n=20) and other medical illnesses 2.3% (n=4). CONCLUSION: CONCLUSION: The current study suggests that in the past 5 years, the main causes of IUD in Hospital USM include infections, congenital anomalies, and unexplained causes. Mothers with GDM or diabetes carry a higher risk.